Non-surgical management of unruptured tubal ectopic pregnancy - Choudhary, Anjali; Chaudhari, Priyanka; Bansal, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is still the leading cause of pregnancy related morbidity in the first trimester. Since majority of the women who present with ectopic pregnancies are sub fertile and young, there is a role for non-surgical options of managing these pregnancies. Expectant and medical management not only serves to conserve the fallopian tubes but also saves women from surgical trauma and morbidity. The objective of this retrospective study was to share our experience of treating un-ruptured tubal ectopic pregnancies conservatively. Methods: Women diagnosed with un-ruptured tubal ectopic pregnancy, fit for conservative /medical management were included. Women with serum beta HCG levels less than 1000 mIU/L were treated expectantly and women with Bet HCG levels >1000 but <10,000 mIU /L were given Injectable methotrixate. Response to treatment was monitored by serial beta HCG levels. Results: Total 37 women included in the study.12% women showed complete resolution with expectant treatment alone and 88% resolved after a single dose methotrixate. Conclusions: Many women with un-ruptured tubal ectopic pregnancies would benefit from expectant management, or methotrixate therapy. Methotrixate used in carefully selected women is safe and effective in resolving these cases with good post treatment reproductive outcome.